On the nanobubbles interfacial properties and future applications in flotation - Calgaroto, S.; Wilberg, K.Q.; Rubio, J. (Minerals engineering, 2014)
•Air nanobubbles were formed after depressurisation of saturated air in reagentized solutions.•Zeta potential values displayed sigmoidal pH behaviour between pH 2 (+26mV) and 8.5 (−28mV).•The nanobubbles had an isoelectric point at pH 4.5.•The size of the nanobubbles depended on zeta potentials, bigger at the isoelectric point or ±5mV (750nm).•Highly charged and small nanobubbles were obtained in the presence of surfactants. Nanobubbles, generations forms, basic studies and applications constitute a growing research area, included their usage in advanced mineral flotation. Yet, there are investigation needs for sustainable generation procedures, stability and understanding the nanobubbles interfacial properties and structures. Results proved that a reduction in pressure makes the super-saturated liquid suffers cavitation and nanobubbles were generated. Medium pH and solutions tested were adjusted, in the air saturation vessel, before the nanobubbles were formed, and this allowed to control (in situ) the surface charge/zeta potential-size of the forming nanobubbles. Measurements obtained with a ZetaSizer Nano equipment showed zeta potential values, in the presence of 10−2 molL−1 NaCl, displaying sigmoidal pH behaviour between pH 2 (+26mV) and 8.5 (−28mV); an isoelectric point was attained at pH 4.5 and were positively charged (up to 23mV) in acidic medium, a phenomenon which has not been previously observed. In alkaline medium, bubbles were highly negative zeta potential (−59mV) at pH 10. The double layers appear to play a role in the formation of stable nanobubbles providing a repulsive force, which prevents inter-bubble aggregation and coalescence. Accordingly, the sizes of the nanobubbles depended on their charge and increased with pH, reaching a maximum (720nm) around the isoelectric point (±5mV). Highly charged and small nanobubbles (approximately 150–180nm) were obtained in the presence of surfactants (10−4 molL−1 of alkyl methyl ether monoamine or sodium dodecyl sulphate); the zeta potential values in these experiments followed a similar trend of other reported values, validating the technique used with the nanobubbles sizes varying with pH from 150 to 400nm. Thus, charged and uncharged stable nanobubbles can be tailor-made with or without surfactants and it is expected that their use will broaden options in mineral flotation especially if collectors coated nanobubbles (“bubble-collectors”) were employed. A detailed and updated review on factors involving stability, longevity and coalescence of nanobubbles was made. It is believed that future trend will be on sustainable formation and application of nanobubbles at industrial scale contributing to widen applied research in mineral, materials processing and liquid effluent treatment by advanced flotation.